Gut microbiota-derived metabolite phenylacetylglutamine inhibits the progression of prostate cancer by suppressing the Wnt/β-catenin signaling pathway - Lv, Jing; Jin, Shengkai; Zhou, Yuhua; Fu, Chaowei; Shen, Yang; Liu, Bo; Li, Jufa; Li, Menglu; Zhang, Yuwei; Feng, Ninghan (Frontiers in Pharmacology, 2025)
BackgroundProstate cancer is one of the most common malignant tumors among men worldwide, and current treatments still face many challenges. Therefore, researchers are continuously seeking new therapeutic methods to improve treatment efficacy and reduce side effects. Phenylacetylglutamine (PAGln), a common metabolite of the gut microbiota, has been reported to have anti-inflammatory and anti-tumor activities.MethodsWe assessed the impact of PAGln on prostate cancer using in vitro and in vivo models. Cell proliferation, migration, and invasion capabilities were evaluated through CCK8, EdU incorporation, and colony formation assays, as well as wound healing and Transwell assays. The in vivo anti-cancer effects of PAGln were evaluated using a BALB/c nude mouse xenograft model of prostate cancer and a lung metastatic tumor model established via tail vein injection. Molecular mechanisms were investigated through qRT-PCR and Western blot analysis.ResultsPAGln inhibited the proliferation, migration, and invasion of prostate cancer (PCa) cells in vitro and suppressed the growth of prostate cancer in vivo. PAGln notably increased the mRNA levels of CCNG2 in PCa cells. Importantly, the knockdown of CCNG2 weakened the effects of PAGln on PCa cells. Mechanistic studies revealed that PAGln could promote the phosphorylation of β-catenin by upregulating CCNG2, thereby inhibiting the Wnt/β-catenin signaling pathway.ConclusionIn summary, PAGln can effectively inhibit the proliferation, migration, and invasion of PCa by upregulating CCNG2 and suppressing the Wnt/β-catenin signaling pathway. These findings suggest that PAGln may serve as a promising therapeutic agent for prostate cancer.